“I’d keep going until somebody said no and nobody ever said no”: exploring identity-strengths amongst medical students from widening participation backgrounds - Smith, Kathrine Gibson; Cleland, Jennifer A.; Walker, Kim; Lumsden, Colin; Laidlaw, Anita (Frontiers in Medicine, 2025)
BackgroundWidening participation is an important consideration in medicine, which has been historically elitist. Despite the evolving evidence base on WP in medicine and advancing of discourse around conceptualizing WP, the identity of students from WP backgrounds remains problematized. Currently, there are few studies exploring how WP medical students have found strength in their experiences of adversity and developed skills which will be an asset to their career. To address this gap, the aim of this study is to understand, using a strengths-based approach, the strengths and resources that WP students draw on to enact success in medicine.MethodsThis is a qualitative study using individual interviews for data collection. We selected the identity-specific strength lens to understand how WP students in medicine draw on their strengths and resources to enact success in pursuing careers in medicine. We recruited eligible students who had completed, or were undertaking, a ‘gateway’ programme and had directly entered the undergraduate medical degree and who had fulfilled university WP criteria prior to entry. Interviews were recorded electronically and transcribed verbatim. Data were coded inductively and in accordance with thematic analysis.ResultsFive main themes were constructed from the analysis. Participants drew on the following strengths and resources to enact success in medicine: (i) Not taking no for an answer: determination and perseverance; (ii) Learning from the past: using their lived experience; (iii) Making things work: resourcefulness; (iv) Drawing on their sense of self: Self-awareness, reflection and independence; and, (v) Growing a support network: Having strong relationships with others.ConclusionThere is still much to be done in creating inclusive environments in medical education which promote belonging and development of diverse values and beliefs. However, using strengths-based approaches can reframe study of widening participation in medicine and shift thinking and discourses from deficit to anti-deficit ways of thinking and discourses.